Sisters of fate : the myths that speak themselves - Hudgens, Michael Thomas (Cambridge Scholars, 2013)
""Tracking the feminine principle in divination over three thousand years, this book ranges from the Oracle at Delphi to Japanese film of the 20th century. At the center of the study is an exploration of the psychic vantage point shared by various sisters.